THE REALIZATION OF SEMANTIC MAPPING STRATEGY IN READING OF ENGLISH FOR FOREIGN LANGUAGE CLASS IN SMK BARDAN WASALAMAN BATANG - S. Thoriqul Huda; Sutinnarto Sutinnarto; Haris Hamdani (Journal of English Language Teaching and Literature (JELTL), 2022)
The purpose of this study is to gain a better understanding of the effectiveness of Semantic Mapping strategies in teaching reading comprehension in second grade students of SMK Bardan Wasalaman Batang. The research question is whether Semantic Mapping strategies are effective in Reading of English for Foreign language Class. Forty-two eleventh grade of in SMK Bardan Wasalaman Batang was chosen as a subject and divided equally into two groups; one group is the experimental group and the other is the control group. There are several procedures carried out in data collection to answer research questions; first, a pre-test is given before the experiment is performed to ascertain whether there are no significant differences in English proficiency in the two subject groups of lesson. Subjects are required to complete a reading comprehension test consisting of forty-five multiple-choice tests within ninety minutes. Second, after the experiment, a post-test was carried out using the same test for the pre-test. Finally, the t-test was used to determine whether there were significant differences in the achievement of reading comprehension between the two groups. The data showed that there were significant differences in the achievement of reading comprehension between the experimental groups - treated with Semantic Mapping strategies and the control group taught with KWL strategy. It means that the Semantic Mapping Strategy is more effective than KWL Strategy. The data indicate that there is significant difference in reading comprehension achievement between the experimental group - treated and Semantic Mapping strategy, and the control group taught with KWL strategy. It means that Semantic Mapping Strategy is more effective than KWL Strategy.